Types and Influence of Social Support on School Engagement of Young Survivors of Leukemia. (August 2016) - Tougas, Anne-Marie; Jutras, Sylvie; Bigras, Marc
The present study aimed to describe and explore the influence of social support on the school engagement of young survivors of pediatric leukemia. Fifty-three young Quebecers, previously diagnosed and treated for leukemia, completed a questionnaire measuring their school engagement and participated in an interview focusing on the support offered by four groups of relations with regard to school: parents, siblings, friends, and other nonprofessional relations. The interview responses revealed that parents were perceived to be the primary source of informational and emotional support, with support also provided to a lesser extent by friends, siblings, and members of the extended family. Inferential analyses indicated that young survivors report a higher school engagement score when they perceive themselves as receiving support from a greater number of groups of relations, especially from friends or siblings.